INTEGRASI IMTAQ DAN IPTEK DALAM MATA KULIAH ILMU KEALAMAN DASAR (IKD/ IAD) - Milya Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
Studying science and technology should not lead Moslems to atheism. Conversely, the more Moslems study science and technology, they more they realize the existence of “the All Controller” of the universe. In fact, Islam encourages its believers to seek for both science and technology based knowledge (aqliyah) and faith based ones (naqliyah). The improvement on faith (imtaq) can well realized through the mastery on science and technology. These two fields are not standing alone or even against one another. In fact, they should in a good integration. Such integration can be implemented through a subject called Ilmu Alamiah Dasar (Basic Science). Through learning and understanding the perfect creation of Allah, one will improve his/her faith and in turn get closer to Him.Kata Kunci: integrasi, imtaq, iptek, ilmu kealaman dasar